2008
DOI: 10.1590/s0100-67622008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da luz e de diferentes temperaturas na germinação de sementes de Heliocarpus popayanensis L

Abstract: espécie arbórea pioneira utilizada no Brasil, principalmente, para restauração florestal. O objetivo desta pesquisa foi avaliar o efeito da luz e da temperatura na germinação das sementes de H. popayanensis. Para análise do efeito da luz, a semeadura foi realizada em caixas de plásticos transparente e preto, mantidas em germinador a 25 °C. Na avaliação do efeito da temperatura foram analisados, em mesa termogradiente, nove intervalos de temperaturas constantes, compreendidas entre 15 °C e 35 °C, e duas alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
3
10
0
5
Order By: Relevance
“…These results reinforce the idea that most tropical and subtropical species show maximum germination potential at temperatures of up to 30°C (MACHADO et al, 2002). In seeds of Heliocarpus popayanensis, the temperature of 35 o C was beneficial to the seeds up to a maximum period of six hours (BRANCALION et al, 2008) as was seen in the present work, in a similar way to that observed in forest clearings. The fact that germination occurs at different temperatures and luminosities of 24 and 12 hours, indicates that the seeds of this species are able to germinate even in small clearings, indicating adaptation to the natural thermal and luminous fluctuations of the environment.…”
Section: Batches -------------------G%-------------------------------supporting
confidence: 88%
See 2 more Smart Citations
“…These results reinforce the idea that most tropical and subtropical species show maximum germination potential at temperatures of up to 30°C (MACHADO et al, 2002). In seeds of Heliocarpus popayanensis, the temperature of 35 o C was beneficial to the seeds up to a maximum period of six hours (BRANCALION et al, 2008) as was seen in the present work, in a similar way to that observed in forest clearings. The fact that germination occurs at different temperatures and luminosities of 24 and 12 hours, indicates that the seeds of this species are able to germinate even in small clearings, indicating adaptation to the natural thermal and luminous fluctuations of the environment.…”
Section: Batches -------------------G%-------------------------------supporting
confidence: 88%
“…both with greater light availability. Brancalion et al (2008) found that for the seeds of jangada brava, although they may have issued a primary root in the dark, the incidence of light also favored the development of the seedlings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para as espécies pioneiras, que normalmente apresentam requerimentos específicos de condições ambientais para germinar em condições de clareira, os regimes de temperatura alternada podem estar relacionados tanto à superação da impermeabilidade do tegumento a água (Vázquez-Yanes e orozco- Segovia, 1982;Baskin e Baskin, 1998;Brancalion et al, 2008) como à alteração no balanço de substâncias promotoras e inibidoras da germinação (Bewley e Black, 1982;Vasquez-Yanes e orozco-Segovia, 1993;marcos filho, 2005), podendo também suprir a necessidade de luz para a germinação de sementes fotoblásticas positivas (godoi e Takaki, 2004). nesse sentido, a exigência de regimes de temperatura diferenciados por parte de algumas espécies pioneiras para a superação da dormência pode dificultar a padronização da temperatura para a germinação, já que, nesses casos, a temperatura pode estar mais relacionada à superação da dormência do que ao favorecimento das reações metabólicas que culminam na germinação.…”
Section: Tabacifoliumvellunclassified
“…In seeds of Peltophorum dubium Sprengel (Taubert), 30°C provided the highest number of seeds germinated in the first count (Oliveira et al, 2008). Brancalion et al (2008) reported that temperatures of 25 and 30°C are the most favorable for the germination of the species, with a relation between the optimum temperature and the biome occurrence of the species.…”
Section: Resultsmentioning
confidence: 99%